EdTech in humanitarian contexts: whose evidence base? - Moser-Mercer, Barbara; AlMousa, Kawkab K.; Alhaj Hussein, Rawan M.; AlSbihe, Rawan K.; AlGasem, Ahmad S.; Hadmoun, Ali A.; Bakkar, Bashar A.; AlQadri, Mohammed H.; AlHmoud, Mohammed M. (Frontiers in Education, 2023)
This paper reports on the design and development of an evaluation toolbox for EdTech deployed in contexts of fragility and crisis. The project adopted a bottom-up approach: training EdTech users in participatory action research approaches was followed by a comprehensive mapping of problems in Azraq refugee camp that might be addressed through the chosen EdTech installed in a local Makerspace. Students as citizen science researchers used a developmental evaluation approach to deepen their understanding of evaluation as a concept and as a process and proceeded to match the results of their Azraq camp problem tree analysis with evaluation questions related to the EdTech tools available in the Makerspace. The paper concludes with a proposed evaluation toolbox, a set of approaches and processes that include research capacity-building in fragile contexts, citizen-science approaches that engage youth, and user-led evaluation that emphasizes the notion of evaluation as a learning process driven by those designed to benefit from EdTech in fragile contexts.